1992
DOI: 10.1136/bmj.304.6830.821
|View full text |Cite
|
Sign up to set email alerts
|

Communication between general practitioners and consultants: what should their letters contain?

Abstract: Objective-To canvass the views of all general practitioners and consultants working in Newcastle upon Tyne on the content of referral letters and replies, the feasibility of standardising certain aspects of referral letters, and the use of communications data for audit purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0
5

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(92 citation statements)
references
References 4 publications
5
79
0
5
Order By: Relevance
“…15 This data-collection sheet was used by the first author to record the presence of the feedback letter from the hospital in the patient records and the details contained in the feedback letter. The quality of the data contained in the feedback letter was assessed by the first author (a clinician) looking at the presence of the following elements that are agreed upon as important in the literature: patient identification, the person who wrote the feedback letter's name and signature, description of the investigations done on the patient, the diagnosis of the patient, any treatment procedures or clinical management and a description of the necessary follow-up care of the patient.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 This data-collection sheet was used by the first author to record the presence of the feedback letter from the hospital in the patient records and the details contained in the feedback letter. The quality of the data contained in the feedback letter was assessed by the first author (a clinician) looking at the presence of the following elements that are agreed upon as important in the literature: patient identification, the person who wrote the feedback letter's name and signature, description of the investigations done on the patient, the diagnosis of the patient, any treatment procedures or clinical management and a description of the necessary follow-up care of the patient.…”
Section: Data Collectionmentioning
confidence: 99%
“…14 Items viewed by both the specialists and the general practitioners as always important to include in the feedback letters were: mention of the patient's problem (symptoms, signs or condition), the clinical management plan, the treating doctor's signature or name, findings on investigation, the follow-up appointment of the patient and a summary of the presenting clinical history of the patient. 15 The South African public health system is characterised by a hierarchical structure and referral system. The role of district hospitals is to provide level one (generalist) services to in-and outpatients referred from PHC clinics and community health centres.…”
Section: Introductionmentioning
confidence: 99%
“…2,7 Clear recommendations have not, however, been made in the dental specialities although McAndrew 4 and Zakrzewska 3 both made suggestions for information needed in a referral letter to a dental consultant. Zakrzewska suggested that the referral should contain administrative details, clinical findings and relevant medical history.…”
mentioning
confidence: 99%
“…45 Studies have shown increased physician satisfaction and better feedback from specialists when referral templates are used to standardize referral communication. 43,46,47 For instance, capturing the reason for consult is a key but often omitted step in the referral process, 13,[48][49][50][51] and thus electronic referrals must be designed to include a clearly defined justification of the referral. Furthermore, communicating details related to urgency is an important component of referral content.…”
Section: Teaching Point 2: Evaluation Must Determine Whether Technolomentioning
confidence: 99%